Study of palmar dermatoglyphic pattern in syndactyly patients - M Y Dofe; M M Meshram (Wolters Kluwer Medknow Publications, 2015)
Background and aims : Syndactyly is congential fusion between fingers which may vary from simple fusion of skin to fusion between bony components of fingers. The aim of this study was to find out the range of dermatoglyphic abnormalities in syndactyly patient because of close association between underlying tissue (derived from mesoderm) and overlying epidermis (derived from ectoderm) during embryogenesis of hand. Materials and methods : Present study was carried out in 20 patients with congenital syndactyly of fingers. The authors evaluated fingertip patterns, axial triradius, palmar pattern, flexion creases, a-b ridge count,digital triradii and pattern intensity. Results : Remarkable dermatoglyphic variations were observed in syndactylous hands, which were rare in normal hands. Conclusion : There are certain specific associations between anomalous hands and dermatoglyphic patterns indicating that underlying mesenchyme influences the development of epidermis derived from ectoderm and so the ridge pattern.